A flavonoid monomer tricin in Gramineous plants: Metabolism, bio/chemosynthesis, biological properties, and toxicology. (1st August 2020) - Jiang, Bo; Song, Junlong; Jin, Yongcan
Highlights: Tricin is associated with numerous health benefits for human nutrition. Tricin shows many unique biological properties for chemoprevention. The structure-activity relationship of tricin monomer is outlined. The bioactivity of tricin is expressed through the signaling cascade reaction. Abstract: Tricin (5, 7, 4′-trihydroxy-3′, 5′-dimethoxyflavone) as a renewable and bioactive polyphenolic compound is widely distributed in monocots with free and conjugated forms. It is derived from the secondary metabolite of plants with an analogous biosynthetic pathway to other flavonoids. Due to its unique biological properties over other flavonoids, tricin has been linked to numerous health benefits for human nutrition. In recent years, tricin has been demonstrated to have excellent pharmacological bioactivities and has been proposed as a safe candidate for cancer chemoprevention. For throwing light on the structure-activity relationship of tricin monomer and its potential clinical application, the natural occurrence, physicochemical characteristics, bio/chemosynthesis, isolation and purification, biological properties involved metabolism in vitro and in vivo of tricin as well as its toxicology and bioavailability are critically reviewed, which aims at greatly moving forward the value-added applications of this natural bioactive material on food, human nutrition, and pharmacology.